MINAT MAHASISWA DALAM BERINVESTASI DI GALERI INVESTASI BEI FAKULTAS EKONOMI DAN BISNIS UNILAK - Wiyati, Rita; Salmiah, Neneng; Wibisono , Rafidianto; Al Amin, Al Amin; Andira, Agung Putra (Komunitas Manajemen Kompetitif, 2024)
The Indonesian Stock Exchange (BEI) Investment Gallery is a means of introducing the Capital Market from an early age to the academic world. One of the private universities in Riau province which has an investment gallery is Lancang Kuning University, which is located at the Faculty of Economics and Business called the BEI FEB Investment Gallery, Lancang Kuning University. The opening of the IDX FEB Investment Gallery at Lancang Kuning University is a collaboration between the BEI Riau region and accompanied by PT Indopremier. With the existence of the Investment Gallery at FEB Unilak since 2018, based on interviews, student interest in investing is still low. The purpose of this research is to determine the low interest of FEB Unilak students in investing in the IDX FEB Unilak Investment Gallery. The results of the research show the symptoms or elements of self-interest of FEB Unilak students to invest in the BEI FEB Unilak Investment Gallery, for students who have invested in themselves they have 3 symptoms, namely the element of cognition (knowledge), the element of conation (willingness) and the element of strong feelings to invest and have hope that in the future there will be profits. Meanwhile, FEB Unilak students who have not invested in the IDX Unilak Investment Gallery have symptoms of elements of cognition (knowledge) that are still small and limited and do not yet have symptoms of elements of conation (willingness) as well as elements of feeling, and it can be concluded that FEB Unilak students' interest in investing is still low. invest in the IDX FEB Unilak Investment Gallery. Keywords: Interest, Investment, knowledge, Investment Gallery